A Review on Recent Developments in The GPS Based Localization and Wireless Sensor Networks - Arpit Namdev (AG Volumes, 2022)
The advancement of the location as well as navigation technologies and procedures has made it easier to locate individuals in difficult and complicated situations. Researchers have been focusing on Wireless Sensor Network (WSN) localization over the last decade or more. A number of recent advances in the GPS location technology are discussed in this article, including applications of such technology in a variety of industries.